CARELESS CHOICES, DREADFUL CONSEQUENCES: A COMPARATIVE STUDY OF W.W. JACOBS’ THE MONKEY’S PAW AND RICHARD MATHESON’S BUTTON, BUTTON - Asmarani, Ratna (Faculty of Humanities, Diponegoro University, 2020)
The purpose of this paper is to analyze the theme of free choices and their relation to the stated consequences embodied in the two short stories, one by W.W. Jacobs entitled The Monkey’s Paw and another one by Richard Matheson entitled Button, Button. The analysis focuses on four aspects; namely, the situational triggers of the free choices, the gripping conflicts in the free choices, the ethical consequences, and the purpose of the twisted endings. The concepts borrowed to support the analysis are the concepts concerning situational choices, morality types, and ethical consequences. The research methods applied in the analysis are the combination of the library research, the textual method enriched with the relevant contexts in order to completely dig out the proposed problems The results of the discussion show that every free choice taken under whatever reason will lead to the stated consequence whether it is unbelievable or impossible. The superstitious atmosphere in The Monkey’s Paw and the mysterious atmosphere in the Button, Button, all lead to the inevitability to avoid the temptation to choose resulting in the disastrous consequences.